Pengaruh Transformasi Digital SDM dan Kompetensi Digital terhadap Kinerja dengan Agility Karyawan sebagai Variabel Intervening PT Jemla Ferry Merak Banten - Putri Tsulistiawati; Erlina Gentari; Dina Aprilia (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The rapid development of digital transformation has prompted organizations to adapt human resource management by leveraging more effective and adaptive technologies. Implementing digital HR transformation and enhancing employees’ digital competencies are key factors in enabling employees to respond to dynamic work environments. This study examines the effect of HR digital transformation and digital competencies on employee performance, with employee agility serving as an intervening variable at PT Jemla Ferry Merak Banten. A quantitative explanatory research design was employed, with data collected via questionnaires distributed to respondents selected through simple random sampling. Data analysis was performed using SmartPLS 4.0, including outer and inner model evaluations. Results indicated that all measurement indicators met validity and reliability standards, with outer loadings >0.70, Average Variance Extracted (AVE) >0.50, and composite reliability >0.70. Structural model testing revealed that HR digital transformation positively influenced employee agility, digital competencies positively affected employee agility, and employee agility significantly improved employee performance. These findings suggest that enhancing the implementation of digital systems and fostering employee digital competencies can strengthen adaptability and flexibility, which in turn enhances performance. The study provides theoretical contributions to the development of digital-based HR management and offers practical insights for organizations seeking to improve human resource quality through digital transformation